Social Policy Without Invariance - Ivarola, Leonardo Abel (2018)
Invariant knowledge is widely considered an effective tool for social policy implementation. This approach is associated with a mode of thought that presupposes (at least) two assumptions: (1) that there exist stable causal factors, and (2) that only one kind of intervention - ex-ante - is relevant for an effective implementation. This paper presents a critique to these assumptions. In particular, it is shown that social processes do not fit the logic of stable causal factors, but they are more suited to the logic of "open-ended-results". On the basis of this ontological variation it will be argued that more than knowledge of invariant factors, the support for an effective policy must be sought in the blueprint constraints and in the possibility of their being satisfied in the target system. Furthermore, it will be shown that permanent interventions are more appropriate than ex-anteinterventions for the social realm.